Originally Posted by

**daigo** Suppose I have to solve for y:

$\displaystyle x\leq 1$

$\displaystyle (x - 1)^{2} = y$

So I know that (x - 1) will always be 0 or a negative, therefore I must take the negative square root of (x - 1):

$\displaystyle -\sqrt{(x - 1)^{2}} = -\sqrt{y}$

Am I to understand that this is the same as:

$\displaystyle -1 \cdot \sqrt{(x - 1)^{2}} = -1 \cdot \sqrt{y}$

$\displaystyle =$

$\displaystyle -1 \cdot (x - 1) = -1 \cdot \sqrt{y}$

$\displaystyle =$

$\displaystyle -x + 1 = -1 \cdot \sqrt{y}$